Information Technology Outsourcing and Successful Knowledge Transfer| An Exploratory Case Study - McGowan, Cynthia (University of Phoenix, 2018)
The purpose of this qualitative exploratory case study was to uncover the perceptions of Information Technology Outsourcing (ITO) project leaders and project teams regarding knowledge transfer between client and vendor partners during the opening and closing transition phases of the ITO projects. Purposeful sampling was used to identify ITO knowledge assets, including project team members as well as documents and artifacts, within the participating organizations that may provide information regarding the knowledge transfer processes during the transition phases of the ITO project. The sample criteria were ITO project team members from one US-based client organization and the US company’s international vendor partners. The study population included project managers, analyst, developers, subject matter experts (SMEs) and other ITO knowledge workers involved in ITO project from one US-based organization. Interview and document analysis was done with the aid of NVivo Pro 11® research software. Four themes emerged from the study participants' responses including (a) KT approaches to plans and processes relative to opening and closing phases of ITO projects; (b) KT dependencies relative to IT project team members reliance on project tools, processes, and artifacts; (c) Determinants of KT success or failure relative to project team member's perceptions; and (d) The role of documentation relative to communication and distribution of KT outcomes. This qualitative exploratory case study may provide insights into additional aspects of knowledge transfer during ITO transition phases, which may be used by IT leaders and project teams to plan for successful knowledge transfer during the transition phases of ITO projects.